2019
DOI: 10.1590/18069657rbcs20180105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Casagrande and Fall Cone Methods for Liquid Limit Determinations in Different Clay Soils

Abstract: How to cite: Crevelin LG, Bicalho KV. Comparison of the Casagrande and Fall Cone methods for liquid limit determinations in different clay soils. Rev Bras Cienc Solo. 2019;43:e0180105.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The first evaluation that can be done is that the Fall Cone method and Casagrande apparatus generally give different values for the liquid limits, as already proven by some researches (Wood, 1982;Leroueil & Le Bihan, 1996;Crevelin & Bicalho, 2019). And when comparing the values between Casagrande and Fall Cone methods, for most samples, it is noticed that the higher values were obtained with the Fall Cone.…”
Section: Resultsmentioning
confidence: 83%
“…The first evaluation that can be done is that the Fall Cone method and Casagrande apparatus generally give different values for the liquid limits, as already proven by some researches (Wood, 1982;Leroueil & Le Bihan, 1996;Crevelin & Bicalho, 2019). And when comparing the values between Casagrande and Fall Cone methods, for most samples, it is noticed that the higher values were obtained with the Fall Cone.…”
Section: Resultsmentioning
confidence: 83%
“…Comparing the LL values of medium plasticity soils, it is observed that the LLCONE values are slightly higher than the LLCUP values, with a difference of less than 6 %. Several researchers have noted that, at lower LL levels, the LLCUP values tend to be slightly smaller than the LLCONE values (Özer, 2009;Zentar et al, 2009;Crevelin and Bicalho, 2019;Niazi et al, 2020) Notably, there are some differences in the results of CPC and FCT tests for soils with high plasticity. In these cases, LLCONE tends to underestimate the LLCUP values by about 16 %.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has several limitations and potential inaccuracies. These include the need for subjective judgment when determining groove closure length, sensitivity to variations in apparatus adjustment techniques, difficulties in maintaining the apparatus, challenges in achieving repeatability, the impact of the cup and base stiffness on results, frequency of drop, wear of the grooving tool, and difficulties in cutting grooves in certain soil types (Wroth and Wood, 1978;Wasti and Bezirci, 1986;Özer, 2009;Spagnoli, 2012;Haigh, 2012Haigh, , 2016El-Shinawi, 2017;Crevelin, 2019). To address these issues, many researchers proposed the fall cone test (FCT) to determine the LL (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Unified Soil Classification System (USCS) recognizes water's role and considers the Atterberg limits to classify silty and clayey soils. Although it is a classification system with a long tradition of use, there are still discussions about the influence of different test methods on the liquid limit value -LL -as in the case of Casagrande apparatus and the fall cone tests (Crevelin & Bicalho 2019;Niazi et al 2020).…”
Section: Introductionmentioning
confidence: 99%